Analysing Clipped Sea-Level Records for Harmonic Tidal Constituents - Evans, J. J.; Pugh, D. T. (The International Hydrographic Review, 2015)
Coastal sea-level measurements must sometimes be made at sites where the gauge dries out at low levels. By progressively removing the lower part of a tidal record, and analysing the remainder with the conventional least-squares criteria, we have obtained stable values of the principal constants until only half of the original range remained. This stability has implications for the definitions of tidal constants and of mean sea level in regions of very shallow water and drying banks.